2018
DOI: 10.3390/insects9010003
|View full text |Cite
|
Sign up to set email alerts
|

The Vivarium: Maximizing Learning with Living Invertebrates—An Out-of-School Intervention Is more Effective than an Equivalent Lesson at School

Abstract: The introduction of living invertebrates into the classroom was investigated. First, possible anchor points for a lesson with living invertebrates are explored by referring to the curriculum of primary/secondary schools and to out-of-school learning. The effectiveness of living animals for increasing interest, motivation, and achievement in recent research is discussed. Next, the Vivarium, an out-of-school learning facility with living invertebrates, is described. The effects of an intervention study with livi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 51 publications
1
16
0
Order By: Relevance
“…First, we investigated the effectiveness of living animals for increasing interest, motivation, and achievement comparing an in school or an out-of-school intervention with living invertebrates. We found that the out-of-school intervention is more effective than an equivalent lesson at school where girls showed higher achievement after treatment than boys (Wüst-Ackermann et al, 2018). Conscientiousness was a predictor of invertebrate-inspired achievement.…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…First, we investigated the effectiveness of living animals for increasing interest, motivation, and achievement comparing an in school or an out-of-school intervention with living invertebrates. We found that the out-of-school intervention is more effective than an equivalent lesson at school where girls showed higher achievement after treatment than boys (Wüst-Ackermann et al, 2018). Conscientiousness was a predictor of invertebrate-inspired achievement.…”
mentioning
confidence: 72%
“…The living invertebrates used were the giant African land snail (Lissachatina fulica), millipedes (Spirostreptidae sp. 6 and Archispirostreptus gigas), phasmids (Eurycantha calcarata, Extatosoma tiaratum, Heteropteryx dilatata, and Phyllium giganteum), the Madagascar hissing cockroach (Gromphadorhina portentosa), and the mealworm beetle (Tenebrio molitor) (Wüst-Ackermann et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…The study encompassed a pre-test, the teaching intervention and a post-test ( Figure 2). As the purpose of the study was also to test which of the conditions, teacher-centered instruction, working at workstations or an out-of-school setting contributes most to the students' knowledge about and attitude towards wolves, the sample was divided into three groups, [36,37]. The teacher-centered School condition and the workshop School condition groups were from the general upper secondary school (School 1).…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have shown that little knowledge about insects exists [ 34 , 35 , 36 ]. Research on student knowledge has often focused on invertebrates or insects in general [ 36 , 37 , 38 , 39 , 40 ]. Other studies have focused on taxa such as beetles, butterflies or ants [ 34 , 41 , 42 , 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, long-lasting effects of knowledge and attitude could be illustrated. Wüst-Ackermann et al [ 38 ] found that an out-of-school intervention is more effective than an equivalent lesson in school.…”
Section: Introductionmentioning
confidence: 99%